Clinical Benefit from Ipilimumab Therapy in Melanoma Patients may be Associated with Serum CTLA4 Levels - Leung, Anna M.; Lee, Agnes Fermin; Ozao-Choy, Junko; Ramos, Romela Irene; Hamid, Omid; O’Day, Steven J.; Shin-Sim, Myung; Morton, Donald L.; Faries, Mark B.; Sieling, Peter A.; Lee, Delphine J. (Frontiers in Oncology, 2014)
Stage IV metastatic melanoma patients historically have a poor prognosis with 5-10% 5-year survival. Ipilimumab, a monoclonal antibody against cytotoxic T-lymphocyte antigen 4 (CTLA4), is one of the first treatments to provide beneficial durable responses in advanced melanoma. However, less than 25% of those treated benefit, treatment is expensive, and side effects can be fatal. Since soluble (s) CTLA4 may mediate inhibitory effects previously ascribed to the membrane-bound isoform (mCTLA4), we hypothesized patients benefiting from ipilimumab have higher serum levels of sCTLA4. We found that higher sCTLA4 levels correlated both with response and improved survival in patients treated with ipilimumab in a small patient cohort (patients with (n=9) and without (n=5) clinical benefit). sCTLA4 levels were statistically higher in ipilimumab-treated patients with response to ipilimumab. In contrast, sCTLA4 levels did not correlate with survival in patients who did not receive ipilimumab (n=11). These preliminary observations provide a previously unrecognized link between serum sCTLA-4 levels and response to ipilimumab as well as to improved survival in ipilimumab-treated melanoma patients and a potential mechanism by which ipilimumab functions.